A bibliometric analysis of Crossref agritourism literature indexed in Web of Science - Dimitrovski, Darko; Leković, Miljan; Joukes, Veronika (Hotel and Tourism Management, 2019)
Agritourism has received growing academic attention over the recent decades. Thus, the current focus on the state of academic knowledge on agritourism provides further insight into the development of thought in the field and a better understanding of the main issues of importance for the academic community in this area. To secure the understanding of the most frequent topics within agritourism literature, the sample of 21 Crossref journals indexed in Web of Science was defined. A bibliometric and keyword analysis served as valuable instruments to assess the current trends within the topic and to predict the future direction of agritourism research. The results of the implemented analysis suggest that the scientific journal of Tourism Management is the most influential journal to spread knowledge regarding agritourism, while Carla Barbieri is recognised as the most influential author in the field. The recently increased interest in rurality on a global scale emphasises the need for more agritourism studies that will be capable of providing valuable guidelines for agritourism providers, tourists, and destination managers.